Effectiveness of Self-Regulated Learning-Based Instruction: Enhancing Student Learning Autonomy (Study on LMS Syam-Ok UNM) - Sayidiman, Sayidiman; Ihsan, Andi; Hartoto, Hartoto; Syamsuddin, Afdhal; Pagarra, Hamzah; Hermuttaqien, Bhakti Prima Findiga (Universitas Negeri Makassar, 2024)
Learning autonomy is becoming essential in the 21st century, demanding individuals to master various fundamental skills. This article explores the self-regulated learning model as a solution to enhance student learning autonomy. A case study conducted in the music arts course at Universitas Negeri Makassar found that students' learning autonomy levels were still low, even among those considered active. Related research also confirms the low learning autonomy of students across various settings. The research methodology employed an experimental approach with a one-group pretest-posttest design. Data collection was carried out by observing student activities through a Learning Management System (LMS) before and after modifying instructional methods. Data analysis results showed a significant difference between pretest and posttest scores, with a notable increase in posttest scores. The findings indicate an improvement in student learning autonomy. Learning autonomy fosters the desire to learn and acquire new knowledge, facilitates individual ownership of learning, and enhances learning independence. The study concludes that modifying instructional methods based on the self-regulated learning model effectively improves student learning autonomy.Keywords: Learning Autonomy, Learning Models, Self-Regulation, Students, Education.